Early Insights from Financial Diaries of Smallholder Households - Anderson, Jamie (World Bank, Washington, DC, 2015)
Renato and Hecinta are raising six young children in a rural area of Mozambique’s northern Nampula Province. On just half a hectare, they grow rice, maize, beans, cashew, peanuts, cabbage, and tomatoes, selling what they can and eating the rest. But, like many of the 475 million smallholder household’s worldwide, agricultural production is just one of their many income-generating activities. They balance several sources of income, within and outside of agriculture, while juggling a range of family needs and using an equally diverse portfolio of financial tools. The Smallholder Diaries will provide a holistic picture of the financial lives of smallholder households not only as agricultural producers, but also as consumers, laborers, and off-farm entrepreneurs. The ultimate goal of this research is to translate the insights from the Smallholder Diaries into financial tools and provider practices that more effectively respond to the needs and preferences of this important client group. Drawing on initial data, this Focus Note shares early insights from the smallholder diaries, providing a first look at how smallholder households weave together agricultural and nonagricultural sources of income and employ a range of financial tools to meet their families’ needs. A nuanced picture of smallholder families will continue to emerge as more data are collected, with increasing focus on how they anticipate and manage risk, make household financial decisions, and leverage a range of financial tools.